The effect of microbial arabinoxylanases on premature yeast flocculation. Issue 3 (16th April 2020) - Shang, Yueling; Wang, Dujun; Cai, Guolin; Sun, Junyong; Li, Fengwei; Lu, Jian; Yu, Xiaohong
Abstract : The use of barley malt infected with microorganisms can induce premature yeast flocculation (PYF) during fermentation. To understand this further, it is necessary to determine the role of microbial enzymes influencing PYF. In this study, the induction of PYF by two arabinoxylanases from Bacillus subtilis (A and B) and one from Aspergillus brasiliensis (F) was investigated. The results showed that all three arabinoxylanases could induce premature yeast flocculation. Husk from PYF negative (PYF‐) malt pre‐treated with arabinoxylanases could induce severe PYF. An increase in enzyme activity resulted in an increase in of PYF. Bound ferulic acid – an important component inducing PYF – increased significantly in the 40% (v/v) ethanol precipitate of wort. However, the ratio of ferulic acid/arabinoxylan in the 40% ethanol precipitate decreased with an increase in arabinoxylanase F, but increased with arabinoxylanases A and B. The addition of the three arabinoxylanases at the beginning of the PYF‐ mashing process showed that the arabinoxylanases A and B could induce PYF with greater intensity than arabinoxylanase F. It can be inferred that the bacterial arabinoxylanases produced more PYF factors than from Aspergillus brasiliensis . The results of this study may provide new insights for further research and focus on the role of bacteria in PYF. © 2020 The Institute of Brewing & Distilling